Urinary bisphenol A and its substitutes exposure increased the risk of renal tubular injury (N-acetyl-β-d-glucosaminidase) in the general Taiwanese population - Yu-Jung Lin; Jung-Wei Chang; Vinoth Kumar Ponnusamy; Vinoth Kumar Ponnusamy; Han-Bin Huang; Hsin-Chang Chen; Po-Chin Huang; Po-Chin Huang; Po-Chin Huang; Po-Chin Huang (Frontiers in Public Health)
BackgroundIt is uncertain if exposure to BPA and its substitutes has an impact on renal function, including N-acetyl-β-D-glucosaminidase (NAG), which is an early marker for kidney injury. We aimed to (1) Estimate the daily intakes (DIs) of BPA and its substitutes using individual urinary levels and conduct the cumulative risk assessment of bisphenols. (2) Assessed the association between exposure to BPA and its substitutes with various renal function indices using a dose-based and cumulative risk assessment approach.MethodsWe recruited 366 participants, and three bisphenols (BPA, bisphenol F, and bisphenol S) were analyzed through ultraperformance liquid chromatography–tandem mass spectrometry. DI levels were calculated for each bisphenol. Hazard index (HI) values were calculated for determining cumulative risk. Using the renal function index, we measured the serum and urinary level (e.g., microalbumin, NAG). The NAG/Creatinine ratio (> 4 IU/g creatinine) and other renal functions indexes based on clinical cut-off points to defined abnormality.ResultsAfter adjustment for covariates, increased NAG/Creatinine ratios were associated with higher DIs of BPA, showing a dose-response trend (Adjusted Odds Ratio [AOR] tertile2: 3.58, 95% CI = 1.52–8.44; AOR tertile3: 7.34, 95% CI = 2.26–23.81; Ptrend < 0.001). Notably, the HI of bisphenols was positively associated with NAG/Creatinine in adults (AOR tertile2= 2.18, 95% CI = 1.10–4.34; AOR tertile3= 4.27, 95% CI = 2.14–8.51) after adjusted for covariates.ConclusionWe found a sensitive risk factor for abnormal NAG/creatinine levels after exposure to BPA and its substitute. Further mechanistic studies are needed to clarify these associations.